Prevalence of augmented renal clearance in a Malaysian intensive care setting - Md Ralib, Azrina; Abd Rahim, Shahir Asraf; Ishak, Nuraisyah; Mat Nor, Mohd Basri (2017)
INTRODUCTION Augmented renal clearance (ARC) is a phenomenon where there is elevated renal clearance and defined by adjusted body weight creatinine clearance > 130ml/min. ARC results in changes of the pharmacokinetic and pharmacodynamic of antimicrobial therapy being administered, which may result in its subtherapeutic dose. We evaluated the prevalence of ARC in critically ill patients with sepsis. METHODS This is an interim analysis of single centre, prospective observational study of critically ill patients. The study has been registered with the National Medical Research Register (NMRR-14-1897-21447) and has obtained ethics approval. Inclusion criteria were patients older than 18 years old with sepsis, defined as clinical infection and acute increase in SOFA score>2, plasma procalcitonin>0.5ng/ml. Only those with plasma creatinine >130 mmol/l were analysed. ARC is defined as eGFR of more 130 ml/min. Cardiac index were measured using the Ultrasonic Cardiac Output Monitoring. eGFR is calculated using the CKD-EPI equation. RESULTS Fourteen patients were analysed so far, of which 7 (50%) had ARC on ICU admission. Of those with ARC, 6 persisted on day 2 and 4 on day 3. In these patients, eGFR correlated well with cardiac index on (r=0.65, p=0.01) on ICU admission. This correlation persisted on day 2 (r=0.56, p=0.04), but not on day 2. There were no differences in the SAPS II or SOFA score between patients with and without ARC (p=0.06 and 0.30 respectively). CONCLUSIONS ARC occur in almost half of critically ill patients with sepsis, and most persisted over the next 3 days of ICU stay. It is correlated with high cardiac index commonly seen septic patients. Hence, adequate monitoring the GFR is needed to evaluate the impact of subtherapeutic dosing of antimicrobial therapy in these patients.